Immunological and Biochemical Markers in Oral Pre-cancer and Cancer : A Study - Sunali Khanna (Journal of Indian Academy of Oral Medicine and Radiology, 2005)
Oral cancer, the sixth most common cancer worldwide remains, continues to be the most prevalent cancer related to the consumption of tobacco, alcohol and other carcinopenic products. Serum levels of circulating immune complexes, trace elements (copper, iron and selemium) were evaluated in 30 patients with OSMF (Oral submucous fibrosis)/leukoplakia, 30 patients with squrmous cell carcinoma and 30 normal subjects. There was a significant increase in the circulating immune complexes in the pre cancer and cancer patients. Serum copper levels showed gradual increase from pre cancer to cancer group. However, serum iron levels were decreaed significantly in the cancer group. Serum selenium levels were also decreased significantly in cancer group. Among, circulating immune complexes, serum copper, iron and selenium the best predictors for the occurrence of lesion were age, serum iron, circulating immune complexes and serum selenium in the decreasing order.